Symbiosis across institutional logics in a social enterprise. Issue 3 (7th November 2016) - Maibom, Cæcilie; Smith, Pernille
Abstract : Purpose: Non-profit organisations are moving from being permeated with social institutional logics to becoming increasingly influenced by market logics. These organisations thereby have to cope with multiple, often conflicting, logics. The existing literature on hybrid organisations has investigated the consequences of multiple logics, focussing in particular on the conflicts and power struggles between the agents of different logics. This paper aims to examine a social enterprise (SE), which in recent years has experienced a shift towards market logics while being firmly grounded in a non-profit social logic. Design/methodology/approach: This paper is a qualitative, single-case case study of a SE based on interviews and observations. Findings: The paper investigates how this hybrid organisation experienced and responded to an organisational environment marked by multiple institutional logics. Unlike the subjects of many previous studies, the organisation managed to accommodate and assemble the logics in an unproblematic symbiosis. A strong ideological congruence across institutional logics appears to play the main role in spanning the boundaries between institutional logics. Furthermore, organisational structures advocating decentralisation, autonomy and transparency appear to be important facilitators of the integration of diverse logics. Originality/value: This paper contributes to the literature on hybrid organisations and SEs and aids practitioners in such organisations. It suggests that organisational decentralisation, autonomy and transparency facilitate the integration of multiple logics – especially if ideological congruence exists between the actors of different institutional logics. The findings indicate that ideological congruence enhances tolerance towards different approaches and increases the willingness to integrate diverse logics.